Prevalence and determinants of Systemic Hypertension in Inhabitants of high altitude of Nepal - Prajapati, Dipanker; Poudel, Pratima; Hirachan, Anish; Sherpa, Kunjang; Sharma, Bharosa; Karki, Dilasha; Yadav, Monica; Dhakal, Santosh; Dewan, Anita; Shakya, Rosy; Tamrakar, Binita; Shakya, Urmila; et al. (Asian Journal of Medical Sciences, 2020)
Background: Several studies have shown increase in prevalence of cardiovascular risk factors in the individuals residing in high altitude in various parts of the world. Aims and Objective: This study was conducted with an aim to estimate the prevalence and determinants of hypertension among the high-altitude population of Jomsom district of Nepal. Materials and Methods: We carried out a prospective camp based survey in Jomsom area on 4th and 5th June of 2017 where we measured the blood pressure, recorded anthropometric measurements like weight, height, BMI, Waist, Hip, Waist/hip ratio and maintained the thorough recorded after verbal consent of the participants. Results: A total of 617 local residents of Jomsom were screened. The mean age was 44.4±17. 6 years with predominant female subjects (53.5% female vs. 46.5% male). Hypertension was present in 142(23.0%) which was significantly lower than in the general population of Nepal as compared to other large scale studies. In addition, alcohol consumption in 29.3%, cigarette smoking in 15.9% and tobacco consumption in 8.3% was present. Higher BMI and waist/hip ratio was significantly associated with male sex and hypertension Conclusion: The overall prevalence of hypertension is lower among the individuals residing in higher altitude compared to the general population although the other determinants are comparable.